2019
DOI: 10.1186/s12889-019-6889-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends and correlates of driving under the influence of alcohol among different types of adult substance users in the United States: a national survey study

Abstract: Background Despite a decrease in driving under the influence of alcohol (DUIA) prevalence over the past decades, DUIA prevalence still remains high in the United States. To date, there is limited research examining whether different types of substance users have different trends in DUIA. This study sought to assess trends and variables associated with DUIA by substance use type. Methods National Survey on Drug Use and Health (NSDUH) is a cross-sectional, nationally repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
3
5
0
1
Order By: Relevance
“…DUI-A, and DUI-C) and with DUI-C (compared with no DUI) after adjusting for sociodemographic characteristics and frequency of alcohol and cannabis use. Findings are in accordance with those of previous research showing the association of simultaneous alcohol/cannabis use with DUI (when compared with concurrent use,26 alcohol use only,28 and fatal crashes 2 ). This study adds to the literature reporting more recent nationally representative data from the U.S. (2016−2019) and compares various types of DUI categories.…”
supporting
confidence: 92%
“…DUI-A, and DUI-C) and with DUI-C (compared with no DUI) after adjusting for sociodemographic characteristics and frequency of alcohol and cannabis use. Findings are in accordance with those of previous research showing the association of simultaneous alcohol/cannabis use with DUI (when compared with concurrent use,26 alcohol use only,28 and fatal crashes 2 ). This study adds to the literature reporting more recent nationally representative data from the U.S. (2016−2019) and compares various types of DUI categories.…”
supporting
confidence: 92%
“…For example, Grondel et al (2018) have suggested the decision to DUICA may be related to beliefs that cannabis can improve driving ability and, therefore, compensate for the impairment effects of alcohol. Indeed, this belief that cannabis use may compensate for alcohol impairment may explain recent evidence that DUICA is more common among cannabis users than noncannabis users (Park & Wu, 2019). Similarly, this explanation is consistent with evidence that drivers testing positive for alcohol are more likely to test positive for other drugs (Lacey et al, 2005).…”
supporting
confidence: 53%
“…Adults with a lifetime CUD were 2.4 times more likely to have lifetime drug-related legal problems. The tendency for alcohol use to intersect the legal system is empirically supported via U.S. research showing that using alcohol (exclusively) had a prevalence rate of 11.71% for driving under the influence (Park & Wu, 2019). Likewise, the educational, occupational, and accident-oriented functional consequences of CUD are arguably the traits or symptoms most likely to catalyze justice-involved or other mandates for treatment.…”
Section: Alcohol and Cannabis Use: Legal And Other Consequencesmentioning
confidence: 99%